2020
DOI: 10.1038/s41598-020-78220-6
|View full text |Cite
|
Sign up to set email alerts
|

Biological and physical approaches on the role of piplartine (piperlongumine) in cancer

Abstract: Chronic inflammation provides a favorable microenvironment for tumorigenesis, which opens opportunities for targeting cancer development and progression. Piplartine (PL) is a biologically active alkaloid from long peppers that exhibits anti-inflammatory and antitumor activity. In the present study, we investigated the physical and chemical interactions of PL with anti-inflammatory compounds and their effects on cell proliferation and migration and on the gene expression of inflammatory mediators. Molecular doc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 90 publications
1
15
0
Order By: Relevance
“…Compounds 6, Before assessing the effects of the Nobiletin-containing fraction (NCF), the Xanthohumolcontaining fraction (XCF), and their combination (Mix) on tumor cells, we studied their impact on the viability of two healthy cell lines. The human stromal cells, HS-5, and the human umbilical vein endothelial cells, HUVEC, have been extensively described as reliable models to estimate and predict the side effects of anti-cancer drugs on healthy cells [44][45][46]. The two cell lines were treated with increasing concentrations of the two fractions for 24 and 48 h and only mild effects on cell viability were observed, supporting the absence of significant toxicity of Nobiletin and Xanthohumol (Figure S1A,B).…”
Section: Nobiletin and Xanthohumol Hamper Cr-csphcs Viability While Sparing Healthy Cellsmentioning
confidence: 57%
“…Compounds 6, Before assessing the effects of the Nobiletin-containing fraction (NCF), the Xanthohumolcontaining fraction (XCF), and their combination (Mix) on tumor cells, we studied their impact on the viability of two healthy cell lines. The human stromal cells, HS-5, and the human umbilical vein endothelial cells, HUVEC, have been extensively described as reliable models to estimate and predict the side effects of anti-cancer drugs on healthy cells [44][45][46]. The two cell lines were treated with increasing concentrations of the two fractions for 24 and 48 h and only mild effects on cell viability were observed, supporting the absence of significant toxicity of Nobiletin and Xanthohumol (Figure S1A,B).…”
Section: Nobiletin and Xanthohumol Hamper Cr-csphcs Viability While Sparing Healthy Cellsmentioning
confidence: 57%
“…Our investigations indicated that PL attenuated systemic and pulmonary inflammatory changes, partially by modulating the expression of the endogenous AnxA1, in lung inflammation induced by cigarette smoke [42]. The potential of PL as a therapeutic immunomodulator for cancer prevention and progression was reinforced by analyzing PL administration in human cancer cells from an epidermoid carcinoma of the larynx (Hep-2) and umbilical vein endothelial cells (HUVEC), in which PL modulated the expression of genes involved in inflammatory processes [36]. Although there are several publications related to PL, few studies have focused on its anti-inflammatory role, and the actions of PL in ocular inflammation are not known.…”
Section: Introductionmentioning
confidence: 88%
“…In recent years, another potent anti-inflammatory mediator, piperlongumine (PL) (5,6-dihydro-1-[(2E)-1-oxo-3-(3,4,5-trimethoxyphenyl)-2-propenyl]-2(1H)pyridinone), a biologically active component of Piper species (Piperaceae), has attracted the attention of our research group for its possible interaction with AnxA1 [36]. In particular, PL is the main alkaloid of long pepper (Piper longum L.), and its pharmacological actions include cytotoxic, antitumor, antiangiogenic, antiplatelet, antibacterial, antidiabetic, antianxiolytic, antiatherosclerotic, and antifungal effects [36][37][38][39][40][41][42][43]. PL induces apoptosis by interfering with redox and reactive oxygen species (ROS) homeostatic regulators, such as glutathione S-transferase pi 1 (GSTP1) and carbonyl reductase (CBR1) [44].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations